RELATIONSHIP OF TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPLE AND TEACHER DISCIPLINE WITH THE QUALITY OF EDUCATION SERVICES - Sri MULANI (Journal of Education and Leadership in Education, 2019)
The purpose of this study was to analyze the relationship between Principal Transformational Leadership and Teacher Work Discipline with the Quality of Education Services in East Jakarta High School. This research uses survey and correlation methods. The study used questionnaires, tests and structured interviews. The number of samples was 145 teacher employees who were randomly selected using the Slovin formula. The results showed that there was a positive relationship between Principal Transformational Leadership and Teacher Work Discipline with the Quality of Education Services in East Jakarta High School. This finding recommends that to improve the quality of teacher services it is recommended to increase the value of transformational leadership and improve teacher work discipline in order to become a culture of teacher virtue in providing good educational services.